Higher Education in the Environmental Century. - Mulkey, Stephen (American Journal of Economics & Sociology, 2017)
The environmental crisis that threatens the future of our species is unprecedented as we begin the 'environmental century.' Natural conditions that were favorable for the development of civilization have been degraded. Climate change has begun to disrupt ecosystems and is likely to undermine agricultural and industrial production, reducing the ability of the global economy to support a growing population. Under these dire conditions, it is imperative that colleges and universities transform themselves into institutions organized around transdisciplinary programs in sustainability science. The curriculum should be oriented around training the future workforce in skills that will be needed in new institutions that seek to adapt proactively to natural systems as they are transformed. Those skills will involve learning to address the dynamic changes of the biosphere rather simply attempting to preserve and restore natural systems to some desired previous condition. Every institution-political, legal, economic, medical, and scientific-will need to be re-aligned to achieve sustainability. Higher education is currently failing to meet this mandate. Sustainability science remains on the margins of academic life, with few resources and little prestige. Faculty are still primarily oriented toward the questions raised within their disciplinary specialties, not toward tasks associated with transdisciplinary problem solving. Reframing higher education to meet the challenges of the environmental century is going to require a revolution in the purposes and structures of the university.